2018
DOI: 10.1093/nar/gky333
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution and analysis of eukaryotic RNase P RNPs

Abstract: RNase P is a ubiquitous site-specific endoribonuclease primarily responsible for the maturation of tRNA. Throughout the three domains of life, the canonical form of RNase P is a ribonucleoprotein (RNP) built around a catalytic RNA. The core RNA is well conserved from bacteria to eukaryotes, whereas the protein parts vary significantly. The most complex and the least understood form of RNase P is found in eukaryotes, where multiple essential proteins playing largely unknown roles constitute the bulk of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Individual depletion of Pop5, Rpp14, Rpp30 or Rpp21, which had little or no effect on RPR stability, also affected RNase P activity and showed accumulation of pre-tRNAs (Figure 3F and G). Rpp21 had the least effect on activity, consistent with the observation that in vitro reconstituted yeast RNase P did not require Rpp21 for activity (7).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Individual depletion of Pop5, Rpp14, Rpp30 or Rpp21, which had little or no effect on RPR stability, also affected RNase P activity and showed accumulation of pre-tRNAs (Figure 3F and G). Rpp21 had the least effect on activity, consistent with the observation that in vitro reconstituted yeast RNase P did not require Rpp21 for activity (7).…”
Section: Resultssupporting
confidence: 84%
“…RPR biogenesis requires association with a specific subset of Rpps: Pop1, Pop4, Rpp20 and Rpp25 (Figures 2–4). The importance of these Rpps can be rationalized based on the high-resolution structures of yeast and human RNase P and in vitro reconstitution of yeast RNase P (7,9,11). Pop1 (∼100 kDa protein) in yeast and human RNase P makes extensive contacts with the RPR and stabilizes the helical core of the RPR’s catalytic domain ((9,11) and Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins Pop6 and Pop7 form a heterodimer that helps to engage Pop1 in both RNase MRP (Fig. 4a ) and RNase P 21 , 22 , 26 , 37 . Pop6 and Pop7 interact with P3 RNA regions that adopt similar folds in RNase MRP and RNase P and are folded similarly in the two enzymes (RMSD = 1.8 Å and 1.3 Å, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…S. cerevisiae RNase MRP and RNase P share eight proteins (Pop1, Pop3, Pop4, Pop5, Pop6, Pop7, Pop8, and Rpp1 (two copies)); RNase MRP protein Snm1 23 has a homolog in RNase P (Rpr2), while Rmp1 24 is found only in RNase MRP. Shared proteins bind to both C- and S-domains 21 , 25 , 26 . Yeast RNase MRP proteins Pop1, Pop3, Pop4, Pop5, Pop6, Pop7, Pop8 have homologs in human RNase P 3 , 4 , 18 , 22 , while Pop3, Pop4, Pop5, and Rpp1 have homologs in archaeal RNases P 3 , 4 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…7a, b) revealed that in 24°C grown pop cells, the level of TLC1 association with Est1 was only~14% of the level in WT cells. In vitro studies suggest that the secondary structures of NME1 and RPR1 are altered in the absence of Pop proteins 24,34 . Therefore, we considered the possibility that the structure of the Est1 and (to a lesser extent) the Est2 binding sites in TLC1 might be Pop protein dependent.…”
Section: Resultsmentioning
confidence: 99%